Schizophrenia treatment with a combination of two LAI antipsychotics: A case report - Jarosz, Marcin; Badura-Brzoza, Karina (Frontiers in Psychiatry, 2022)
Prevention of relapse a psychotic episode is a challenge for schizophrenia treatment. Patients suffering from schizophrenia experience from a few to a dozen relapses in their lifetime. The use of long-acting injectable (LAI) antipsychotics in treatment of schizophrenia is associated with less frequent recurrence of psychotic symptoms, better compliance and better quality of life. The aim of the study is to present the case of succesfull management of treatment-resistant schizophrenia in persistently non-compliant patient using a combination of typical and atypical depot antipsychotics. Because of non-adherence (irregular controls in out-patient clinic) in patient's previous history clozapine was not considered as a therapeutic option. The patient stared to be treated by olanzapine LAI in dose 300mg fortnightly, because good response and tolerance was reported in previous treatment. The treatment was carried out for several weeks and because of the persistence of the constants delusions, liability of affect and tendency to aggressive behavior second antipsychotic was added – zuclopenthyxole initially administered orally.  After four weeks of combined treatment patient’s mental state has improved. The delusions were not reported and the mood was much more stable. Zuclopenthyxole was switched to depot form due to patient’s history of persistent non-compliance, superficial illness’ criticism and the risk of being aggressive to other people. Zuclopenthyxole decanoate in dose 200 mg was administered fortnightly. Patient was discharged from hospital without any symptoms of delusions and hallucinations. In clinical presentation dominated negative symptoms such as avolition and diminished in social activity.  Patient tolerated the management well. Sedation and extrapyramidal symptoms were not observed. The injections were continued alternately (one injection per week) to obtain regular visits in out-patient clinic.